ANALISIS MOTIVASI KERJA GURU KONTRAK DI KOTA KUPANG - Nggandung, Yeheskial (Universitas Nusa Cendana, 2023)
In essence, people work not only to maintain their survival but also aim to achieve a better standard of living. This study aimed to determine the effect of status PNS, salary, sense of security, appreciation, and self-actualization on the work motivation of contract teachers in Kupang City. The population in this study were contract teachers who taught in kindergarten, elementary, middle, high, and Vocational Schools in Kupang City (49 people). The data analysis technique used is multiple linear regression analysis (SPSS 17). The results of the t-test show that each independent variable, namely civil servant status, salary, sense of security, appreciation, and self-actualization needs, affects the work motivation of contract teachers in Kupang City. The calculated t values for each variable are civil servant status = 6,529, salary = 4,828, sense of security = 3,064, appreciation = 2,835, from self-actualization = 2,054 > t table = 2,00. Likewise, the results of the f-test show that all independent variables influence the work motivation of contract teachers. This can be seen from the value of Fcount = 26.577 > Ftable = 3.42 (sig 0.005).